2005
DOI: 10.7748/ns2005.09.19.52.47.c3950
|View full text |Cite
|
Sign up to set email alerts
|

Chronic venous leg ulcers: effect of a community nursing intervention on pain and healing

Abstract: Results from this study have implications for health professionals providing care for clients with chronic leg ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 0 publications
0
42
0
11
Order By: Relevance
“…Some reported healing in groups receiving standard care—at ≤12 weeks, ranging from 23.5% to 45.1%; at 24 weeks: 38.5%; at 6 months: 73.6%; and at 12 months: 67.7% . Some reported healing in groups receiving specialist care—at ≤12 weeks, ranging from 43.6% to 73.0%; and at 24 weeks: 57.6% . In a group receiving specialist care, 96.8% of low‐risk patients and 25.0% of high‐risk patients healed in 24 weeks…”
Section: Resultsmentioning
confidence: 99%
“…Some reported healing in groups receiving standard care—at ≤12 weeks, ranging from 23.5% to 45.1%; at 24 weeks: 38.5%; at 6 months: 73.6%; and at 12 months: 67.7% . Some reported healing in groups receiving specialist care—at ≤12 weeks, ranging from 43.6% to 73.0%; and at 24 weeks: 57.6% . In a group receiving specialist care, 96.8% of low‐risk patients and 25.0% of high‐risk patients healed in 24 weeks…”
Section: Resultsmentioning
confidence: 99%
“…Studies on patients with chronic leg ulcers have reported the average duration of these ulcers is around 12–13 months [2,3], around 60–70% of patients have recurring ulcers [4], 24% of patients are hospitalised because of the ulcers and most people suffer from the condition for an average of 15 or more years [3]. Care for chronic wounds is reported to cost 2-3% of total health care spending in developed countries [5,6] and these costs are set to rise with ageing populations [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is evident that pain, exudate, odour, and the psychological impact of unsightly wounds and bandages often result in limited and impaired mobility, embarrassment and subsequent © NURSING STANDARD / RCN PUBLISHING social isolation (Persoon et al 2004, Edwards et al 2005a. Brown (2005b) discussed how chronic leg ulcers affect a person's social life and subsequently cause social isolation.…”
Section: Social Isolationmentioning
confidence: 99%
“…Because patients with leg ulcers are usually treated at home, community nurses are often the only social contact the patient will have (Edwards et al 2005a). This level of social contact is considered insufficient in meeting factors that are essential for effective management of leg ulceration, such as the need for peer support, information and empathy (Lindsay 2001).…”
Section: Social Isolationmentioning
confidence: 99%